2010
DOI: 10.1364/ol.35.003994
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of high harmonics generated by field steering of electrons in a two-color orthogonally polarized laser field

Abstract: We demonstrate enhancement by 1 order of magnitude of the high-order harmonics generated in argon by combining a fundamental field at 1300 nm (10(14) W cm(-2)) and its orthogonally polarized second harmonic at 650 nm (2 × 10(13) W cm(-2)) and by controlling the relative phase between them. This extends earlier work by ensuring that the main effect is the combined field steering the electron trajectory with negligible contribution from multiphoton effects compared to the previous schemes with 800/400 nm fields.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 13 publications
0
34
0
Order By: Relevance
“…Other applications include the field-free orientation of molecules [16][17][18], the generation of high-harmonic spectra [19][20][21][22] and probing atomic and molecular orbital symmetry [23][24][25].…”
mentioning
confidence: 99%
“…Other applications include the field-free orientation of molecules [16][17][18], the generation of high-harmonic spectra [19][20][21][22] and probing atomic and molecular orbital symmetry [23][24][25].…”
mentioning
confidence: 99%
“…This scheme, involving only a frequency doubling crystal, was extensively investigated over the past years. In particular, it was established that harmonic pulses, containing both odd and even orders, can be generated with improved efficiency [22][23][24][25][26] compared with single-colour harmonic generation. The polarization of the harmonics, generated in such a specific case of orthogonally polarized o and 2o laser fields in a centrally symmetric gas medium, was not measured so far and was expected to be linear 27 .…”
mentioning
confidence: 99%
“…In addition, a new set of parameters becomes available to control the HHG emission through the twodimensional steering of the continuum electron by the bi-chromatic field [7]. It has been shown that two orthogonally polarized fields can be successfully used for imaging atomic wavefunctions [8] or the generation of shorter attosecond pulses [9,10]. It has been proposed that by controlling the relative phase of the two pulses, long and short trajectory selection can be achieved [11].…”
mentioning
confidence: 99%